2017
DOI: 10.1371/journal.pone.0186770
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness among adults with cystic fibrosis in Texas, 2004–2013: Patterns of ICU utilization, characteristics, and outcomes

Abstract: ObjectiveAvailable reports on critically ill adults with cystic fibrosis (CF) suggest improving short-term outcomes. However, there is marked heterogeneity in reported findings, with studies mostly based on single-centered data, limiting generalizability. We sought to examine population-level patterns of demand for critical care resources, and the characteristics, resource utilization, and outcomes of ICU-managed adults with CF.MethodsWe used the Texas Inpatient Public Use Data File to identify ICU admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The study was determined to be exempt from formal review by the Texas Tech Health Sciences Center's Institutional Review Board due to use of a publicly available, deidentified dataset. Parts of the methods described below were previously reported [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study was determined to be exempt from formal review by the Texas Tech Health Sciences Center's Institutional Review Board due to use of a publicly available, deidentified dataset. Parts of the methods described below were previously reported [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Early reports suggested that intubation and mechanical ventilation usually failed 20 . However, more recently, over half of intubated and ventilated patients survived to discharge from the ICU 21,22 . In addition, a growing body of literature describes successful respiratory support of patients with noninvasive ventilation, which has been shown to stabilize lung function 23 and can serve as a bridge to transplantation.…”
Section: Improvements In Pulmonary Therapy and Other Complicationsmentioning
confidence: 99%
“…Although outcomes remain guarded, survival associated with intensive care unit (ICU) admission for individuals with ACFLD has improved compared to previous decades, particularly in those with “reversible” conditions (eg, hemoptysis, pneumothorax) and when LTx is an option 43,44 . Among 1711 CF admissions requiring invasive mechanical ventilation, a 2019 study found a hospital survival of 55% even with excluding admissions where LTx was an option 45 .…”
Section: Introductionmentioning
confidence: 99%